Vegetation Analysis and Environmental Relationships of Qatar’s Depression Habitat - Ahmed Elgharib; María del Mar Trigo; Mohamed M. Moursy; Alaaeldin Soultan (Plants, 2025)
Despite Qatar’s depressions being ecologically significant for biodiversity in arid desert regions, they remain poorly studied. This study aimed at assessing the floristic diversity of Qatar’s depression habitat and examining the key environmental drivers shaping vegetation patterns. We applied multivariate analyses, including Canonical Correspondence Analysis (CCA) and Two-Way Indicator Species Analysis (TWINSPAN), to understand the environmental factors that shape vegetation communities and classify the depression sites. A total of 139 plant species from 35 families were recorded from 26 depression sites across Qatar. Both therophytes and chamaephytes were the dominant life forms. Biregional chorotypes were the most prevalent among phytogeographical groups. CCA indicated that grazing pressure, latitude, nitrogen concentration, clay content, and soil pH were among the variables that influenced the vegetation patterns of depressions, while longitude and soil carbon content showed marginal significance in explaining the observed floristic variation. TWINSPAN classified the sites into four distinct clusters, each associated with specific indicator species and habitat conditions. Northern depressions supported higher species richness compared to central and southern depressions, which are dominated by sandy soils and experience intensive grazing patterns that reduce the floristic diversity and limited regeneration of key shrubs such as Vachellia tortilis (Forssk.) Galasso & Banfi. This study helps fill a critical knowledge gap about Qatar’s depression habitat, enhancing efforts to conserve these vulnerable ecosystems, identify ecological threats, and better understand patterns of species distribution across arid landscapes.